Papil Edema - Syarifah Rohaya; Chibratul Husna (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2024)
Papilloedema is a disease that refers to swelling of the optic disc due to increased intracranial pressure (ICP). The etiology of papilledema is things that increase intracranial pressure. Idiopathic intracranial hypertension can cause increased intracranial pressure. Increased intracranial pressure can be seen in clinical and radiological manifestations such as headaches and decreased cerebral blood flow. So to diagnose someone with papilledema, anamnesis, physical examination, and supporting examinations such as fundoscopy, Optical Coherence Tomography / OCT, and perimetry can be carried out. Management for papilledema is aimed at addressing the causes of increased ICP. In cases of masses, surgical management may be indicated. the term idiopathic intracranial hypertension was used, and management of the patient's symptoms was with acetazolamide and weight loss. Surgical procedures such as optic nerve sheath fenestration are considered when vision is considered to be seriously compromised. Ventriculoperitoneal and lumboperitoneal shunts are other surgical interventions that can reduce ICP by draining CSF. Venous sinus stenting is considered in patients with IIH where there is significant transverse venous sinus stenosis.